PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Annisa Syafitri; Ristanti Akseptori; Arfiana Dewi (Proceeding Maritime Business Management Conference, 2024)
Employee performance is the main factor for companies to improved quality and competed with other companies. This study aims to examine the effect organizational culture on employee performance with work motivation as an intervening variable. Based on the problems, performance and work motivation tend to fluctuate and decline. The implementation of organizational culture is not optimal. This type of research is explanatory research which is quantitative with data collection techniques using questionnaires. The selected sample is a saturated sample with fifty-one permanent employees. Validity and reliability tests are used in this study for testing instruments with hypothesis testing using multiple linear regression analysis, path analysis and sobel tests. The results of the study indicate that the variables of organizational culture have a positive effect on employee performance. Partial organizational culture have a positive effect on employee performance and work motivation can mediate the effect between organizational culture on employee performance, therefore, companies need to improve the optimization of organizational culture and work motivation to improve employee performance.